Juridical Analysis of Use of Health Social Security Agency Card as a Condition for Transfer of Land Rights - Sri Yuliana Febri Anti (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to examine and analyze the juridical implications of using the Health Social Security Administering Body card as a condition for the transfer of land rights in Kendari City, to examine and analyze the juridical implications of the transfer of land rights that do not use the Health Social Security Administering Body card as well as to examine and analyze sample deed of sale. The research approach method used in this thesis is a sociological juridical legal research method. This research specification uses descriptive analysis. The types of data used in this study are primary data and secondary data. Collecting research data with interview techniques and study of documents or library materials. The theory used is the Theory of Legal Certainty according to Gustav Radbruchm and Theory of Legal Work according to William J. Chambliss and Robert B Seidmen. The results of the study show that: First, the juridical analysis of the use of health social security agency cards as a condition for the transfer of land rights in Kendari City is based on Gustav Radbruchm's theory of legal certainty because legal certainty as one of the legal objectives can be said to be part of an effort to achieve justice. There is a priority scale that must be implemented, where the first priority is always justice, then benefit, and finally legal certainty. Second, the juridical implications of the transfer of land rights that do not use the BPJS card based on the theory of the working of the law of William J Chamblis and Robert. The connection is what action a role holder will take in response to legal regulations, highly dependent and controlled by the applicable legal regulations of the sanctions of its implementing activities. Third, the sample of the sale and purchase deed has fulfilled all the requirements of the applicable laws and regulations.